Insights of english teaching as community outreach developed by students of the University of El Salvador in different institutions in San Salvador - Coreas, Jacquelinne Elizabeth; Ayala, Josimar Ernesto; Cornejo Rodríguez, Neftalí Alberto; Henríquez López, Claudia Beatriz; Rodríguez, Francisco Antonio; Garay Salinas, Ricardo
The research project “Insights of English teaching as Community Outreach developed by students of the University of El Salvador in different Institutions in San Salvador” represents a special analysis of the different ways in which a foreign language may have incidence in people who are learning for personal, professional and academic purposes.This paper compiles information gathered through an instrument among the benefited people immersed in the different projects served by students of the Foreign Language Department, besides, it contains theoretical information that supports the previous information; this data has been carefully classified in different chapters in order to have readers recognize its diverse components easily and have an appreciation of what the results of this research project has released.